2009
DOI: 10.1111/j.1872-034x.2009.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and its implication for peripheral immunologically‐competent cells to the liver in patients with HBV‐related acute‐on‐chronic liver failure

Abstract: The abnormal prevalence of circulating and intrahepatic ICCs possibly acts as an important factor that may drive the progression of HBV-related ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Previous data from our laboratory have indicated that both mDCs and pDCs infiltrate extensively the liver of ACLF patients and have expressed mature phenotypes. 8,14 Therefore, this DC migration from the blood to the liver may lead to the decreased DC numbers found in the blood, while infiltrated DCs in liver may be involved in the pathogenesis of ACLF. This study found that the decreased numbers of mDC at baseline was associated with a high mortality of ACLF patients and further indicated that the mDC numbers of the host may determine the outcome of ACLF patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous data from our laboratory have indicated that both mDCs and pDCs infiltrate extensively the liver of ACLF patients and have expressed mature phenotypes. 8,14 Therefore, this DC migration from the blood to the liver may lead to the decreased DC numbers found in the blood, while infiltrated DCs in liver may be involved in the pathogenesis of ACLF. This study found that the decreased numbers of mDC at baseline was associated with a high mortality of ACLF patients and further indicated that the mDC numbers of the host may determine the outcome of ACLF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many different cell types, including T lymphocytes, monocytes and DCs, are primed in ACLF, and these are believed to play a pivotal role in the pathogenesis of this disease. [6][7][8][9][10][11] Corticosteroids have been used for the treatment of severe acute hepatic failure by either oral or intravenous administration. Mechanically, corticosteroids can suppress the effects of activated macrophages, DC subsets and other inflammatory cells, [10][11] which indicates that there is a reciprocal effect on the efficacy of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations